KUPU-KUPU DALAM KARYA SENI GRAFIS TEKNIK LINOLIUM CUT - Alviwigo Dwi Putra, Drs. Ariusmedi, M.Sn (Universitas Negeri Padang, 2019)
Indonesia is the largest archipelago country in the world that has a diversity of flora and fauna. Butterfly is one type of fauna that is widely found in Indonesia, which has a beauty and uniqueness, especially on its wings and metamorphosis which is widely admired by humans. The purpose in making this final work is to visualize the shape, uniqueness and beauty of the butterflies which are then poured into graphic works with the Linolium Cut technique. The manifestation of the work is carried out through several stages, namely: the preparation, elaboration, synthesis, concept realization and completion stages.Keywords: butterflies, beauty, graphics arts